Answer:
![y = (-1)/(4)x + (-27)/(4)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/sr47e5tjv7ibraoht5ywptiywxxrj3p2w6.png)
Explanation:
The equation of a line is:
y = mx + b
Where:
m = slope
b = y-intercept
First thing we need to do is solve for the slope. The slope formula is:
![m = (y_2-y_1)/(x_2-x_1)](https://img.qammunity.org/2021/formulas/mathematics/college/v6jhydeui2twqaqea1hoz45m9krvcw4ikp.png)
Where:
x₁ = x-coordinate of the first point
x₂ = x-coordinate of the second point
y₁ = y-coordinate of the first point
y₂ = y-coordinate of the second point
We are given the following points:
Point 1: (-3, -6)
Point 2: (5, -8)
So let's plug in our coordinates into the slope formula:
![m = (y_2-y_1)/(x_2-x_1)\\\\ =((-8)-(-6))/(5-(-3))\\\\ =(-2)/(8)\\\\ =(-1)/(4)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/wpdb0rosch2iyv5rli35xgi65kh18zjqwz.png)
So we have our new equation of this line:
![y = (-1)/(4)x + b](https://img.qammunity.org/2021/formulas/mathematics/middle-school/6mkj6rb3w86iywxinendw4w20hohcpbwe7.png)
What do we do then about the y-intercept?
Our points will help us out by plugging them in our equation, so we can solve for our y-intercept (b).
Let's do both to show that it would be the same:
Point 1 (-3, -6)
![y = (-1)/(4)x + b\\\\-6 = (-1)/(4)(-3) + b\\\\-6 = (3)/(4) + b\\\\-6 = (3)/(4) + b\\\\subtract (3)/(4)\;from\;both\;sides\;of\;the\;equation\\\\-6- (3)/(4)= (3)/(4)- (3)/(4)+b\\\\\\(-24-3)/(4)=0+b\\\\\\-(27)/(4) = b](https://img.qammunity.org/2021/formulas/mathematics/middle-school/jwjfdiw38f4pa07dqh7i39alsbp3132ewx.png)
Point 2: (5, -8)
![y = (-1)/(4)x + b\\\\-8 = (-1)/(4)(5) + b\\\\-8 = (-5)/(4) + b\\\\-8 = (-5)/(4) + b\\\\subtract (-5)/(4)\;from\;both\;sides\;of\;the\;equation\\\\-8- (-5)/(4)= (-5)/(4)- (-5)/(4)+b\\\\\\(-32-(-5))/(4)=0+b\\\\\\(-27)/(4) = b](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ws8sleeffzmw86b0ez7dg33f41jmnitwqf.png)
Now that we have b, we can insert that into the equation of the line:
![y = (-1)/(4)x + b\\\\y = (-1)/(4)x + (-27)/(4)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/pumu15ool4up5exn2mp2xjys79epyfrm3m.png)